Achilles Rupture Repair: Modified Gift-Box With a Proximal Myotendinous Backup Fixation Technique - Nicholas D. Cominos, B.S.; Joseph S. Tramer, M.D.; Andrew J. Peace, M.D.; Matthew A. Zaborowicz, M.D.; Erik B. Eller, M.D.; Lafi S. Khalil, M.D. (Arthroscopy Techniques)
Achilles tendon tears are not an uncommon injury, with a predominance in explosive athletes and weekend warriors in the third to fifth decade of life. Consideration of operative intervention is commonplace in young athletes, whereas less active and older individuals may opt for nonsurgical treatment. Surgical treatment is reported to improve functional outcomes in high-demand individuals and demonstrates increased plantarflexion power, better return to sports rates, and a reduced rerupture rate. Traditionally, a primary end-to-end repair of the Achilles tendon was the surgical treatment of choice. More recently, alternative advanced techniques and minimally invasive constructs have been proposed in an effort to improve repair construct while reducing soft tissue complications. This technical note describes a technique that combines a modified gift-box primary repair with backup fixation using calcaneal anchors. This technique is performed with a small, medially based incision that reduces wound and nerve complications, while promoting end-to-end tendon healing by reducing tension across the repair site through the calcaneal backup fixation.